2017
DOI: 10.1155/2017/6213871
|View full text |Cite
|
Sign up to set email alerts
|

Field Experiment on Soaking Characteristics of Collapsible Loess

Abstract: In collapsible loess area, migration of soil moisture often causes the temporal discontinuity and spatial nonuniformity of collapsibility, which leads to great damage for infrastructures. Therefore, the research on water infiltration is the key to solving the problem of collapsibility. The aim of this paper is to investigate the spatiotemporal evolution of infiltration characteristics of collapsible loess. A field soaking experiment was conducted on collapsible loess in western China, in which a soaking pool w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Specifically, the soil of some loess tunnel foundations was not compact, or it had a high moisture content, which caused difficulty in constructing the tunnel invert. In addition, many tunnel foundations were located in collapsible loess [24,25]; when confronted with water, these foundations would settle unevenly [26][27][28][29], which would cause further cracking in the lining structure [30][31][32]. Additionally, some loess tunnels swelled, making the inverted curvature difficult to maintain [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the soil of some loess tunnel foundations was not compact, or it had a high moisture content, which caused difficulty in constructing the tunnel invert. In addition, many tunnel foundations were located in collapsible loess [24,25]; when confronted with water, these foundations would settle unevenly [26][27][28][29], which would cause further cracking in the lining structure [30][31][32]. Additionally, some loess tunnels swelled, making the inverted curvature difficult to maintain [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the uniform pressure applied on the surface of the soil, as illustrated in Figure 4(b), is not caused by the superstructure. e application of uniform pressure is equivalent to the effect of water on loess to some extent to force the occurrence of displacement, which can be used to analyze the equivalent amount of collapsible deformation [4,5]. e schematic diagram of the two methods is illustrated in Figure 4, and the input calculation parameters are displayed in Table 3.…”
Section: Comparison Of Modulus Reduction Methods and Force-water Equivalent Methodsmentioning
confidence: 99%
“…For instance, the in situ test and field wetting test can directly measure the deformation amount and estimate the deformation characteristics of collapsible loess, and the obtained test data are accurate and reliable. Scholars [1][2][3][4][5] have implemented a significant number of field wetting tests in different areas to collect valuable measured data. e field wetting test conducted in Pucheng Power Plant in Shaanxi Province, China, is one of the representatives [2].…”
Section: Introductionmentioning
confidence: 99%
“…e results of model tests showed that the volumetric moisture content of the slope region where the localized failure initiated was noted reaches a nearly saturated value. Wang et al [21] investigated the soil-atmosphere interaction for foundation by numerical analysis using data from Nairobi. It was further noted that the migration of moisture and the vertical movement within the foundation are obviously affected by rainfall and evapotranspiration.…”
Section: Introductionmentioning
confidence: 99%